A COMPARATIVE STUDY ON DIGITAL-BASED AND NON-DIGITAL-BASED LEARNING MANAGEMENTS IN SANATA DHARMA UNIVERSITY YOGYAKARTA - Dalyono, C. Teguh; Mudayen, Y. M.V. (International Journal of Indonesian Education and Teaching (IJIET), 2017)
This study aims to: 1) determine whether there is a significant difference in effectiveness of learning management by lecturers of USD who use Digital Learning Resources (SBD) with those who do not use SBD based on the students’ perception; 2) determine whether there is a significant difference in the ability of the lecturers who use the SBD and those who do not use SBD in managing the courses according to the students’ perception; 3) determine whether there is a significant difference in the ability of the lecturers who use SBD and those who do not use SBD in empowering students according to the students’ perception. This study analyzes the effectiveness of learning management among 38 lecturers USD who consisted of 19 lecturers who use SBD and 19 lecturers who do not use SBD. The data analysis uses independent difference sampling t-test technique. The results of the study are as follows: First, there is a significant difference in the effectiveness of the lecturers who use SBD with those who do not use SBD in learning management according to the students’ perception with t-value of 2.405 and asymptote significance (2-tailed) of 0.022 smaller than alpha 0.05. Second, there is a significant difference in the ability of lecturers who use the SBD with those who do not use SBD in managing the course according to the students’ perception with t-value of 2.210 and asymptote significance (2-tailed) of 0.041 smaller than alpha 0.05. Third, there is no significant difference in the ability of lecturers who use SBD with those who do not use SBD in empowering students with t-value of 2.627 and asymptote significance (2-tailed) 0.013 smaller than alpha 0.05.doi.org/10.24071/ijiet.2017.010109